Plantar warts on primary lymphedema. - Mazzotta, F.; Del Vecchio, S.; Troccoli, T. (European Journal of Pediatric Dermatology, 2007)
A case of plantar warts arising on primary lymphedema scarcely responsive to topical treatment is reported.